A 3D Covalent Organic Framework with Exceptionally High Iodine Capture Capability. Issue 3 (14th December 2017) - Wang, Chang; Wang, Yu; Ge, Rile; Song, Xuedan; Xing, Xueqing; Jiang, Qike; Lu, Hui; Hao, Ce; Guo, Xinwen; Gao, Yanan; Jiang, Donglin
Abstract: Using porous materials to cope with environmental issues is promising but remains a challenge especially for removing the radioactive vapor wastes in fission because of harsh adsorption conditions. Here we report a new, stable covalent organic framework (COF) as a porous platform for removing iodine vapor—a major radioactive fission waste. The three‐dimensional COF consists of a diamond topology knotted by adamantane units, creates ordered one‐dimensional pores and are highly porous. The COF enables the removal of iodine vapor via charge transfer complex formation with the pore walls to achieve exceptional capacity. Moreover, the 3D COF is "soft" to trigger structural fitting to iodine while retaining connectivity and enables cycle use for many times while retaining high uptake capacity. These results set a new benchmark for fission waste removal and suggest the great potential of COFs as a designable porous material for challenging world‐threatening pollution issues. Abstract : A new 3D covalent organic framework is designed to constitute an eightfold interwoven diamond net structure and 1D open channels with π‐conjugated pore walls. Merging the structural hardness and softness renders the framework with ultrahigh iodine‐uptake capacity, high retention, quick release, and robust reusability, setting a new benchmark porous material for radioactive iodine removal.